The Relationship between Watching Mukbang and Stress Level with Eating Patterns in Adolescents at PB Soedirman Bekasi Islamic High School - Salsabillah, Salwa; Noerfitri, Noerfitri (Media Gizi Indonesia, 2024)
In adolescence, unhealthy eating habits are sometimes formed, because teenagers usually have preferred food choices. Many teenagers think that by eating a lot and having a full stomach, their nutritional needs are met. Unregulated eating habits can be affected by stress. The current trend is watching “mukbang”, the stimulus generated in the form of sound can affect eating behavior. This study aims to determine the relationship between watching mukbang and stress levels and eating patterns in adolescents. The design of this study was a cross sectional study that was conducted at PB Soedirman Islamic High School in Bekasi. There were 138 people aged 16–18 years, who were selected by consecutive sampling. Data collection used the Mukbang Addiction Scale (MAS), Perceived Stress Scale (PSS), and FFQ. Based on the results of the Chi-Square statistical test, a p-value of 0.193 was obtained with an OR of 1.565 for the relationship between the habit of watching mukbang and eating patterns, and a p-value of 0.022 with an OR of 2.258 for the relationship between stress levels and eating patterns. The conclusion of this study is that there is no significant relationship between the habit of watching mukbang and eating patterns, and there is a significant relationship between stress levels and eating patterns in adolescents at PB Soedirman Islamic High School, Bekasi.